Discovery to e-discovery of information: legal frameworks in Malaysia, the United Kingdom and the United States - Mohamed, Duryana (Infonomics Society, United Kingdom, 2013)
Discovery or disclosure involves a process whereby parties to the action disclose to each other documents in their possession, custody or control as a preparation for trial. This process started in England since the Nineteenth Century. At present the civil procedure in England is governed by the Civil Procedure Rules (CPR) 1998. While in Malaysia the Rules of Court 2012(RC) govern the civil procedure at both Subordinate courts and the High courts. Discovery process is governed by Part 31 of CPR and Order 24 of the RC. However, unlike the United Kingdom (UK) CPR the rule on discovery in Malaysia has not emphasized on the importance of e-discovery. There is also no specific provision in the RC or Practice Direction that contains guideline on e-discovery. This paper will analyse on the application of e-discovery in the UK, the United States (US) and Malaysia by studying the existing legal frameworks. The challenges to e-discovery and the possible changes that need to be done on discovery process in Malaysia will also be highlighted.